Teologi sebagai Pelayan Kesosialan: Pemikiran Mazhab Frankfurt tentang Teologi - Tukan, Berto (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2013)
Frankfurt School’s thought on theology was influenced by Karl Marx’s ideas and the psychoanalysis of Sigmund Freud. Generally the Frankfurt School focused its attention on the life of the society and the culture. Concerning theology, only a few discussions of this School which relate the determinism of economy on theology, like that in Marx, tending towards historiographical and psychological analyses. This article summarizes some points of the Frankfurt School based on James Swindal’s “Critical Theory, Negative Theology, and Transcendence.” First, it will discuss briefly the thoughts of Karl Marx and Sigmund Freud on theology and religion. From these two thinkers the School draws some inspirations. Second, it will explain some points of Swindal’s thought about the School’s opinion on theology with its four representatives mentioned in his writing: Benjamin, Horkheimer, Adorno, and Habermas. Third, In reading Swindal’s view, this article need to explain the case of Benjamin’s thought especially the latter’s view of theology. Fourth, by way of a conclusion, this article will recapitulate the line of thought and draw the relevance of the Frankfurt School’s thought on theology for contemporary readers.